The robbery of nature : capitalism and the ecological rift - Foster, John Bellamy; Clark, Brett (Monthly Review Press, 2020)
Bridges the gap between social and environmental critiques of capitalism. In the nineteenth century, Karl Marx, inspired by the German chemist Justus von Liebig, argued that capitalism's relation to its natural environment was that of a robbery system, leading to an irreparable rift in the metabolism between humanity and nature. In the twenty-first century, these classical insights into capitalism's degradation of the earth have become the basis of extraordinary advances in critical theory and practice associated with contemporary ecosocialism. In The Robbery of Nature, John Bellamy Foster and Brett Clark, working within this historical tradition, examine capitalism's plundering of nature via commodity production, and how it has led to the current anthropogenic rift in the Earth System.